Report on the alterations and amendments necessary in the present system of sale and mortgage of land in Ireland - Longfield, Robert (Social Inquiry Society of Ireland, 1853)
It will be found convenient in the following report, to adopt the division naturally suggested by the subject proposed for my examination; and accordingly I shall treat in their order, first, of the present system of selling and mortgaging land in Ireland; secondly, of the leading features of the modes of sale and mortgage in the United States ; and thirdly, the various regulations for the same objects in the principal states of Europe. From a consideration of these I shall proceed to intimate the alterations necessary for the amendment of the prominent defects of our system, and making it more cheap, certain, and expeditious. It may, perhaps, by some be deemed unnecessary to detail the causes, or mode of procedure, by which the powers of sale and mortgage are so Ireland so impeded; but without some attention to the details and technicalities of an old and artificial code of rules relating to our landed property, the differences of other systems would be imperfectly understood, and the alterations suggested as necessary might seem too vague and empirical.
Dated April 1st, 1853
Keywords: Property; Ireland; Land ownership; Land tenure; 314.15